119 NeuroToolkit CSF biomarkers track the progression of Alzheimer's disease at very early stages. Issue 6 (27th May 2022) - Molinuevo, JL; Salvadó, G; Kollmorgen, G; Milà-Alomà, M; Blennow, K; Zetterberg, H; Farrar, G; Suarez-Calvet, M; Gispert, JD
Abstract : Introduction: NeuroToolkit is a set of cerebrospinal fluid (CSF) biomarkers developed to identify Alzheimer's disease co-pathologies, identify and characterize disease progression and treatment response. We assess the association between NeuroToolkit biomarkers and cerebral amyloid deposition in the ALFA+ cohort [1]. Methods: 326 cognitively unimpaired individuals from the ALFA+ cohort [1] underwent a lumbar puncture and amyloid [18F]flutemetamol PET imaging. Biomarkers in NeuroToolkit (Figure 1) were determined using prototype Roche Elecsys® assays. CSF pTau levels were measured using the Elecsys® CSF assay. We cal- culated cross-correlation values between NeuroToolkit biomarkers and Centiloids. Voxel-wise associations between NeuroToolkit biomarkers and [18F]flutemetamol images were sought, accounting for the effect of various demographics. Additional analyses were performed after correcting also for the Aα42/40 ratio or Centiloid values. Results: Figure 1. Shows associations between NeuroToolkit biomarkers and Centiloids. NeuroToolkit bio- markers were significantly associated with cerebral amyloid deposition measured by [18F]flutemetamol PET (Figure 2). Correcting for global amyloid deposition, higher levels CSF YKL-40, an astroglial activity marker, were associated to increased cerebral amyloid deposition in the inferior and lateral temporal lobe, in parietal and orbitofrontal areas, and the caudate heads (Figure 3). Conclusions: Results of NeuroToolkit biomarkers support early involvement of the astroglial response to cerebral amyloid deposition. Disclosure: This study was conducted through a collaboration with Roche Diagnostics International. These data will be presented at Advances in Alzheimer's and Parkinson's Therapies. Ref: Molinuevo. TRCI 2 (2016) 82–92 gwendlyn.kollmorgen@roche.com